The Effect of Sulphate Doping on Nanosized TiO2 and MoOx/TiO2 Catalysts in Cyclohexane Photooxidative Dehydrogenation - P. Ciambelli; D. Sannino; V. Palma; V. Vaiano (International Journal of Photoenergy)
The effect of sulphate doping of titania in promoting activity and selectivity of MoOx/TiO2 catalysts for the cyclohexane photooxidative dehydrogenation has been investigated in a gas-solid fluidized bed reactor. Sulphate and/or molybdate-modified titania catalysts were prepared by incipient wet impregnation of nanosized (5–10 nm crystallite size) samples. At 60% of titania surface coverage by MoOx, sulphate surface density was obtained up to 19 μmol/m2 without formation of MoO3. The catalysts were characterized by N2 adsorption-desorption at −196∘C, micro-Raman and UV-visible reflectance spectroscopy, thermogravimetric analysis coupled with mass spectroscopy (TG-MS), and mass titration. Unsulphated and sulphated titania are both active in cyclohexane total oxidation, but sulphate doping of titania has a detrimental effect on the reaction rate. On Mo-based catalysts, polymolybdate species enabled sulphated titania to convert cyclohexane to benzene (99% selectivity) and cyclohexene, reducing at zero the formation of CO2. Cyclohexane conversion to benzene is almost linearly dependent on sulphate surface density, resulting in enhanced yield to benzene. The enhanced photooxidative dehydrogenation activity and benzene yield by sulphate doping could be attributed to the increase of surface acidity and, as a consequence, of cyclohexane adsorption.